Perspectives surrounding brain donation among African American research participants in the Northwestern University Alzheimer's Disease Center: Developing topics. (7th December 2020) - Dyslin, Deborah Nicole; Dunlop, Sara Rose; Aldridge, Brenda; Tillotson, Robin; Morhardt, Darby
Abstract: Background: Alzheimer's and related dementias (ADRD) disproportionately affect the African American community. Increased participation of African Americans in research is essential to further understand factors related to risk and resilience to ADRD. Brain donation remains the only mechanism to confirm a diagnosis of neurodegenerative disorders and is less common among African American research participants compared to White research participants across the US. Previous studies identified knowledge of brain donation, religious and or funeral plans, family support of decision, and distrust of medical/research community as important factors in African American participation in brain donation. However, perspectives of African American participants within the Mesulam Center ADRC are unknown. Methods: Seven focus groups, stratified by both cognitive and decision status were conducted as part of this analysis. Focus groups ranged in attendance from 2‐8 participants, plus 2‐4 study personnel. 34 research participants and/or study partners participated in this project. Focus groups were co‐facilitated by Northwestern social workers, a Northwestern neuroscience PhD student, and a social work intern at the regional senior center. All focus group discussions were audio recorded, subsequently de‐identified, transcribed and coded for emerging themes. Result: Qualitative analysis revealed several themes: personal connection to memory loss or dementia; altruism; personal decision making, spirituality/religion; historical and current trauma related to healthcare and research; trust; representation of African Americans in clinical and research settings, and understanding the purpose and process of brain donation. Participant identified next steps include community education initiatives centered around brain donation, building trust between the community and research institutions, and increased community engagement by Northwestern in diverse communities. Conclusion: Overall, our findings are consistent with previous findings. Themes highlight the issue of trust, importance of increased representation of African Americans among staff in aiding participation, lack of understand of the purpose and value of brain donation, and the need for purposeful acknowledgement of past traumas by the medical research community. Next steps include both community level and institutional interventions to aid in increased participation in brain donation among African American research participants.